PRINCIPAL'S LEADERSHIP IN DEVELOPING PAI CURRICULUM AT SMK MUHAMMADIYAH 2 WATES YOGYAKARTA: KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGEMBANGAN KURIKULUM PAI DI SMK MUHAMMADIYAH 2 WATES YOGYAKARTA - Wahyu Widi Purnama, Hendro Widodo, Rizky (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
This study aims to analyze the principal's leadership in developing the Islamic Religious Education curriculum. This research uses a qualitative method with a case study approach. Principal leadership is the ability to mobilize existing resources in schools, while teacher pedagogical competence is the ability to manage learning activities. This study aims to describe the principal's leadership and teachers' pedagogical competence at SMK Muhammadiyah 2 Wates. This research used descriptive qualitative case study method. The principal has carried out his leadership role by mobilizing teachers and staff to actively participate in the implementation of the school's vision and mission, in the form of direction from the principal to teachers in learning. The PAI program of SMK Muhammadiyah 2 Wates adopts a stand-alone program in accordance with the instructions of the DIKDASMEN Assembly of PWM DIY